2018
DOI: 10.1080/00224499.2018.1480744
|View full text |Cite
|
Sign up to set email alerts
|

Revisiting the Role of Impulsivity and Compulsivity in Problematic Sexual Behaviors

Abstract: Impulsivity and compulsivity are transdiagnostic features associated with clinically relevant aspects of psychiatric disorders, including addictions. However, little research has investigated how impulsivity and compulsivity relate to hypersexuality and problematic pornography use. Thus, the aims of the present study were to investigate (a) self-reported impulsivity and compulsivity with respect to hypersexuality and problematic pornography use and (b) the similarities and possible differences between hypersex… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

12
97
1
3

Year Published

2018
2018
2024
2024

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 181 publications
(113 citation statements)
references
References 103 publications
12
97
1
3
Order By: Relevance
“…However, effect sizes were low for these factors, which might indicate that facets of impulsivity do not contribute substantially to an unregulated IP use. This result is consistent with the results by Bőthe et al (2018). Following the assumptions of the I-PACE model (Brand, Young, et al, 2016), it is possible that effects of these trait variables on the symptom severity are moderated or mediated by affective and cognitive responses.…”
Section: Discussionsupporting
confidence: 90%
See 2 more Smart Citations
“…However, effect sizes were low for these factors, which might indicate that facets of impulsivity do not contribute substantially to an unregulated IP use. This result is consistent with the results by Bőthe et al (2018). Following the assumptions of the I-PACE model (Brand, Young, et al, 2016), it is possible that effects of these trait variables on the symptom severity are moderated or mediated by affective and cognitive responses.…”
Section: Discussionsupporting
confidence: 90%
“…With regard to a general tendency to act impulsively, research indicates that unregulated IP use is at least weakly associated with higher levels of trait impulsivity Bőthe et al, 2018;Wéry, Deleuze, Canale, & Billieux, 2017). This might indicate that trait impulsivity is a predisposing factor for unregulated IP use but might not be the aspect that differentiates the best between recreational and unregulated IP use (also see Bőthe et al, 2018).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The contribution of personality factors to ratings of CSB symptoms was examined in 10 studies. 77,[103][104][105][106][107][108][109][110] In a study of Shimoni and colleagues, 103 81 women and 186 men were recruited via internet sites used for finding sexual partners. Results of this investigation showed that women (as compared to men) obtained lower scores on Sexual Addiction Screening Test (SAST), 111 they were less open to experiences and more neurotic (as assessed by the Big Five Index).…”
Section: Personality Traitsmentioning
confidence: 99%
“…In the case of trait impulsiveness and compulsiveness, Bőthe and colleagues 104 investigated its relation to PPU and CSB symptoms on a large community sample of 13,778 individuals (4151 females). Regardless of gender, PPU was weakly associated with impulsivity and compulsivity.…”
Section: Personality Traitsmentioning
confidence: 99%